Kinerja Program Studi Administrasi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta (Ditinjau dari Pelayanan dalam Bidang Kurikulum, Sistem Pembelajaran, dan Suasana Akademik) - Wahyuningrum, Dewi Ariyani; Rugaiyah, Rugaiyah; Rahmawati, Desi (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2017)
Research conducted at the Administration of Education Study Program Faculty of Education, State University of Jakarta. This reasearch aimed to describe the performance of the study program in providing good educational services for students as learners through curriculum applied by the program of study which includes the performance of courses in the curriculum development system is supported by learning and academic atmosphere. This study is an evaluative method deskripstif conducted to see the performance of Administration of Education Study Program Faculty of Education, State University of Jakarta using a qualitative and quantitative approach. Evaluation model used is the model Discrepancy Evaluation Model (DEM). The data obtained by researchers is through observation, interviews, and documentation. Key informant interviews were conducted to the Chairman of Study Program UNJ AP FIP, and is supported by a supporter informant consisting of lecturers, TU Staff, and Student Study Program UNJ AP FIP. The reasearch concluded that 1) the performance component of courses on aspects of curriculum development shows the categories very good, 2) the performance component of courses there are aspects of the implementation of learning systems, from four (4) aspects of the implementation of the learning system there are two components indicate the category of very good: execution learning process, efforts to improve the learning system. Components of the implementation of the guiding thesis showed good category. While the implementation of the components of academic guidance indicates less category. 3) the performance component of study program there is the aspect of increasing academic atmosphere, showing very good category. Based on the acquisition of these three components, it can be said the performance of the study program of Educational Administration Faculty of Education at the Jakarta State University Curricula Aspects, Learning Systems and academic atmosphere showed very good category.